Phase II study of cetuximab in combination with docetaxel in patients with recurrent and/or metastatic squamous cell carcinoma of the head and neck after platinum-containing therapy: a multicenter study of the Arbeitsgemeinschaft Internistische Onkologie - Knödler, Michael; Gauler, T. C.; Gruenwald, V.; Matzdorff, A.; Schroeder, M.; Dietz, A.; Jordan, W.-O.; Arnold, D.; Hennemann, B.; Hofele, Christof; Weissinger, F.; Eberhardt, W.; et al. (Oncology, 2013)
Cetuximab and docetaxel have single-agent activity in squamous cell carcinoma of the head and neck (SCCHN). The efficacy of their combination was evaluated in platinum-pretreated patients with recurrent and/or metastatic SCCHN. Patients and Methods: A total of 84 patients were treated with docetaxel 35 mg/m2 weekly for a maximum of 6 cycles and concomitant cetuximab 250 mg/m2 weekly until disease progression or unacceptable toxicity. The primary endpoint was the objective response rate and secondary endpoints included the response rate in relation to platinum sensitivity, progression-free survival (PFS), overall survival (OS) and toxicity. Results: Nine (11%) patients achieved a partial response and 34 (40%) stable disease, resulting in a disease control rate of 51%. Response to treatment was 49% in previously platinum-sensitive and 50% in previously platinum-resistant disease. The median PFS was 3.1 months and the median OS 6.7 months. The most common grade 3 or 4 adverse events were mucositis (8%), pneumonia (8%), fatigue (8%) and skin reactions (14%). Sepsis occurred in 3 patients. Conclusion: Cetuximab plus docetaxel is an active treatment regimen with moderate toxicity in SCCHN patients. However, no superiority in comparison with monotherapy could be shown. Responsiveness and survival were independent of previous platinum sensitivity.
Gesehen am 07.06.2022